Presentation of the Dossier on Public Policies and Education Management - Freitas, Vinicius da Silva (2024)
The dossier on Public Policies and Education Management gathers articles presented at Conpepe – National Congress of Research and Practices in Education. It is a fundamental initiative for academic deepening and critical reflection on educational policies and management processes. We thank the Estudos Interdisciplinares journal for the opportunity to disseminate this work, which aims to promote a broader and deeper understanding of the dynamics involved in the development and implementation of effective public policies in the field of education. This dossier brings together studies that cover everything from theoretical formulation to educational management practices, highlighting the need for well-founded public policies to ensure quality education. The current moment is marked by rapid technological transformations and innovations that profoundly impact the educational field. The integration of new technologies and innovative methods in pedagogical practices and educational management is an emerging topic that demands continuous attention from researchers and educational managers. This dossier seeks to explore how these innovations can be effectively incorporated into public policies and management processes, promoting an education better suited to contemporary needs.